2016
DOI: 10.18805/ar.v37i2.10735
|View full text |Cite
|
Sign up to set email alerts
|

Plant derived smoke stimulation for seed germination and enhancement of crop growth: A review

Abstract: Smoke is an important factor involved in fire and post fire germination cues. The role of smoke in stimulating germination was first highlighted in South Africa in a study on Audouinia capitata, a threatened fynbos species. Farmers throughout the world have traditionally used fire and smoke in grain drying practices. It is thought that these methods improve germination and seedling vigor. Smoke has been applied in agriculture mainly by two ways viz., Aerosol method and Smoke water method. In aerosol method, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The positive and stimulating effects of smoke solutions on germination and plant development were also demonstrated in many previous studies (Ghebrehiwot et al, 2012;Kamran et al, 2013;Govindaraj et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The positive and stimulating effects of smoke solutions on germination and plant development were also demonstrated in many previous studies (Ghebrehiwot et al, 2012;Kamran et al, 2013;Govindaraj et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…More recently, the positive effects of smoke and smoke product-derived plant materials on germination and plant growth have been reported (Govindaraj et al, 2016). It was reported that smoke components encouraged germination (De Lange and Boucher, 1990) and played an important role in the breakdown of dormancy (Light et al, 2002(Light et al, , 2004Van Staden et al, 2004;Ghebrehiwot et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…All these results showed that there were positive and stimulating effects of priming with oat and grass pea derived smoke solutions on growth and forage quality of hydroponic barley and wheat. Previous studies showed that plant derived smoke solutions have stimulating effect on the germination and seedling growth of Poacea families (Ghebrehiwot et al 2012), lettuce (Kamran et al 2013) and a threatened fynbos species (Govindaraj et al 2016). However, the effectiveness of smoke solution in hydroponic system was first mentioned in this study.…”
Section: Resultsmentioning
confidence: 65%
“…In tomato seeds, NO scavengers maintained seed dormancy and counteracted the stimulating effect of fluridone 98 . It is well known that smoke is commonly used in horticulture to break dormancy and promote seed germination of some vegetables, such as lettuce and celery 99 . It is now clear that NO is among the essential active compounds responsible for seed germination stimulated by smoke.…”
Section: Current Understanding Of No Biosynthesis and Bioactivitymentioning
confidence: 99%